Donor Sperm, Lineage, and Preventive Islamic Legal Reasoning: A Sadd al-Dharīʿah Analysis - Salma Salma; Jarudin Jarudin; Aisy Rafiqa Nafsa; Hamadah Ashfiya (Indonesian Journal of Islamic Law, 2026)
Artificial insemination using donor sperm represents a significant challenge to the integrity of lineage (nasab) within contemporary legal and social systems. As a form of assisted reproductive technology, it enables non-conventional forms of procreation that raise complex ethical, legal, and social concerns, particularly regarding kinship, identity, and marital legitimacy. Among the most notable cases is the fertility fraud incident in Indianapolis, where a physician inseminated numerous patients with his own sperm without their knowledge or consent, resulting in extensive and unintended biological relations. This study examines the legal and ethical implications of donor sperm insemination through the framework of sadd al-dharīʿah as a form of preventive Islamic legal reasoning. Employing a qualitative approach based on library research and content analysis, the study draws on documentary materials, including the Our Father case, as well as relevant legal and theoretical literature. The analysis focuses on how reproductive technologies, when detached from normative constraints, generate risks that extend beyond individual cases to broader social structures and systems of lineage governance. The findings indicate that donor sperm insemination poses serious risks to the preservation of lineage (ḥifẓ al-nasl), potentially leading to genealogical ambiguity, inadvertent consanguinity, and disruptions in family structure. Within this context, sadd al-dharīʿah provides a relevant analytical framework for anticipating and preventing harm by restricting practices that may lead to legally and socially undesirable consequences. This article contributes to the ongoing discourse on Islamic legal reasoning by demonstrating the applicability of preventive principles in addressing emerging bioethical challenges, while situating lineage not only as a matter of individual rights but also as a concern of social order and legal ethics.